2015
DOI: 10.1213/xaa.0000000000000090
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Continuous Quadratus Lumborum Block for Postoperative Analgesia in a Pediatric Patient

Abstract: Quadratus lumborum block is a recently introduced variation of transversus abdominis plane block. In this report, we describe the use of ultrasound-guided continuous quadratus lumborum block for postoperative analgesia in a 7-year-old child scheduled to undergo radical nephrectomy (left-sided) for Wilms tumor. The result was excellent postoperative analgesia and minimal requirement for rescue analgesics. The modification described may allow easier placement of a catheter for continuous infusion of local anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 7 publications
0
82
1
4
Order By: Relevance
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…4 In the past few years, several case reports have shown that the QLB has also been successful in providing postoperative pain relief. [5][6][7][8] In a previous randomized control study, we compared the QLB against a control group, in which we intentionally moved our point of injection from the original anterolateral side of the quadratus lumborum muscle to the posterior wall (QLB type 2). 9 This has become our standard practice, as we have abandoned the anterolateral approach completely subsequent to publication of our magnetic resonance study on optimal point of insertion and dispersion of local anesthetics.…”
mentioning
confidence: 99%
“…Injection here should result in visible spread along the anterior (ventral) surface of QLM, and some authors have described modifications that deliberately advance the needle tip into this location. 39,200 In contrast, the QL2 block is an injection on the posterior (dorsal) surface of QLM, in the plane between QL and the investing layer of thoracolumbar fascia that separates it from the overlying latissimus dorsi or paraspinal muscles (Fig. 11).…”
Section: Us-guided Quadratus Lumborum Blockmentioning
confidence: 99%
“…Ultrasound guided Quadratus lumborum block (QLB) block is a new technique of regional analgesia [3,4]. There have been reports of excellent post-operative pain management with the QLB for both abdominal and retroperitoneal surgery [5,6]. However, postoperative analgesia by bilateral transmuscular quadratus lumborum blocks (TQLB) or QL-3 block with catheter is rarely reported.…”
Section: Introductionmentioning
confidence: 99%